Green Fatwas in Bahtsul Masāil: Nahdlatul Ulama's Response to the Discourse on the Environmental Crisis in Indonesia - Moh. Mufid (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2020)
AbstractThis article aims to discuss environmental issues in the Nahdlatul Ulama (NU) tradition as a response to the phenomenon of the environmental crisis in Indonesia. This article answers the question of what is the social context that underlies the birth of the fatwas with ecological nuances among Nahdlatul Ulama? and how is the contribution of Nahdlatul Ulama in realizing eco-literacy among Nahdliyin? The results of the study indicate that the emergence of ecological fatwas or green fatwas was based on the concern of the Nahdlatul Ulama Executive Board as the largest Islamic organization in Indonesia who realized that the phenomenon of the environmental crisis in Indonesia was increasingly concerning. The idea to respond to this environmental crisis phenomenon has occurred since the 29th NU Congress in Cipasung, Tasikmalaya, West Java. The contribution of the Nahdlatul Ulama (NU) through the Bahtsul Masail Institute in realizing an environmentally conscious society (eco-literacy) is by formulating ecological nuances from a fiqh perspective as a guide for Nahdliyin in interacting with its environment in a friendly and sustainable manner. In this context, Nahdliyin residents are obliged to fight for the values of environmental preservation (jihād bi'iyah) as a manifestation of the ethical-ecological responsibility of the khalīfah on earth. (Artikel ini bertujuan mendiskusikan respon Nahdlatul Ulama (NU) terhadap fenomena krisis lingkungan di Indonesia. Ia membidik konteks sosial yang melatari lahirnya fatwa-fatwa bernuansa ekologis di kalangan Nahdlatul Ulama serta konstribusinya dalam mewujudkan eco-literacy di kalangan Nahdliyin. Hasil kajian menunjukkan bahwa lahirnya fatwa-fatwa ekologis atau green fatwas dilatari keprihatinan Pengurus Besar Nahdlatul Ulama yang menyadari bahwa fenomena krisis lingkungan di Indonesia semakin memprihatinkan. Gagasan untuk merespon terhadap fenomena krisis lingkungan ini telah muncul sejak Muktamar NU ke-29 di Cipasung, Tasikmalaya, Jawa Barat. Konstribusi Nahdlatul Ulama (NU) melalui forum Bahtsul Masail dalam mewujudkan masyarakat yang sadar lingkungan (eco-literacy) adalah dengan merumuskan fatwa-fatwa bernuansa ekologis dalam perspektif fiqh sebagai panduan bagi Nahdliyin dalam berinteraksi dengan lingkungannya secara ramah dan berkelanjutan. Dalam konteks ini, warga Nahdliyin diwajibkan memperjuangkan nilai-nilai pelestarian lingkungan hidup (jihād bi’iyah) sebagai manifestasi tanggungjawab etis-ekologis khalīfah di bumi)